The Principle of Divinity in Islamic Communication Perspective - Tengku, Walisyah; Faridah,; A. Fikri Amiruddin Ihsani, (Mediakita, 2023)
This research aims to highlight a core element in an Islamic Communication principle as the Basic Principle, namely the Principle of Divinity, which originated by Zainal Arifin (2021). He intends to signify the existence of the value of God as its principle. He also notes that God is the Basic Principle of Islamic Communication, the core element referring to the spiritual dimension. It is exciting to discuss because during this time, generally, Islamic Communication scholars or experts only stress the normative aspects as ethics without alluding to the spiritual size. They dominantly discuss the ethical to do as Moslems in daily communication with others. One of which is Hamid Mowlana (1996 and 2007), in a previous period highlighting tauhid as the principle, but still, the substance does not describe the spiritual dimension of the Creator. Accordingly, this qualitative research was designed by the library method analyzing some kinds of literature or references to reinforce the view that the basic divinity principle is the Principle of Islamic Communication. Among them is the literature from Zainal Arifin's thoughts, where he clearly explains that the Basic Principles of Islamic Communication are based on the Principles of God. Then the foundations of the Principles of God give birth to reflections in the Muslim community's daily lives. As a result, this research shows that the Divine Principle, where Allah as The Creator, is an absolute element that must exist in every sequence of existing communication elements. This is proven by several sayings of Moslems in their lives reflecting such conditions as the analysis of this study.